La escalada del crimen en la mentalidad del siglo XVI en una relación de sucesos de 1588 - Sánchez Pérez, María (El Colegio de México, 2011)
This paper presents a study and an edition of a “caso horrible y espantoso”,composed by Benito Carrasco and printed in 1588 in a “pliego sueltopoético” (poetic chapbook). The aim of this kind of compositions is toinform about some facts, but also to amuse and to move audiences, as wellas to spread certain ideological interests. The analysis of the story showsthe mentality of the sixteenth-century society towards crime and sin, inaccordance with the principles that emerged after the Council of Trent.